2020
DOI: 10.1021/jacs.0c09200
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Activatable Raman Probes for Simultaneous Detection of Plural Enzyme Activities

Abstract: Raman probes based on alkyne or nitrile tags hold promise for highly multiplexed imaging. However, sensing of enzyme activities with Raman probes is difficult because few mechanisms are available to modulate the vibrational response. Here we present a general strategy to prepare activatable Raman probes that show enhanced Raman signals due to electronic preresonance (EPR) upon reaction with enzymes under physiological conditions. We identified a xanthene derivative bearing a nitrile group at position 9 (9CN-JC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 30 publications
2
68
0
Order By: Relevance
“…Indeed, a large number of interesting sensors have been developed based on xanthenes 29 , 38 , 39 , the parent structures of MARS probes. In fact, a very recent work reported MARS-derivatized probes for detecting enzyme activities 40 . Hence, we expect MARS probes to make important contribution to the multiplexed sensing applications.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a large number of interesting sensors have been developed based on xanthenes 29 , 38 , 39 , the parent structures of MARS probes. In fact, a very recent work reported MARS-derivatized probes for detecting enzyme activities 40 . Hence, we expect MARS probes to make important contribution to the multiplexed sensing applications.…”
Section: Discussionmentioning
confidence: 99%
“…By using isotopically edited nitrile they were able to simultaneously detect four different enzymes. 34 Inherent nitrile in molecules like anticancer drug neratinib, plant fungicides azoxystrobin and chlorothalonil have been used for imaging their distribution. 77,78 Most recently, photoswitchable Raman probes with nitrile groups have been reported that can be turned on and off with different wavelengths of light.…”
Section: Raman Tagsmentioning
confidence: 99%
“…33 This technique has huge potential in biological imaging. 34 Advances in SRS imaging techniques and applications have been reviewed elsewhere. [35][36][37][38][39] 1.1.3 Coherent anti-Stokes Raman scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2013 Royal Society of Chemistry. Panel (C) is adapted from ref ( 89 ). Copyright 2020 American Chemical Society.…”
Section: Detection Of Cellular Uptake and Accumulation Of Specific Labeled Moleculesmentioning
confidence: 99%
“…Overall, the detected enzyme activities were in agreement with their expression levels as assessed by PCR. 89 …”
Section: Detection Of Cellular Uptake and Accumulation Of Specific Labeled Moleculesmentioning
confidence: 99%